2017
DOI: 10.1038/s41598-017-06302-z
|View full text |Cite
|
Sign up to set email alerts
|

The asymmetric impact of global warming on US drought types and distributions in a large ensemble of 97 hydro-climatic simulations

Abstract: Projection of future drought is often involved large uncertainties from climate models, emission scenarios as well as drought definitions. In this study, we investigate changes in future droughts in the conterminous United States based on 97 1/8 degree hydro-climate model projections. Instead of focusing on a specific drought type, we investigate changes in meteorological, agricultural, and hydrological drought as well as the concurrences. Agricultural and hydrological droughts are projected to become more fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 81 publications
0
19
0
Order By: Relevance
“…The spatiotemporal variations in the irrigation effect found in our results highlight the strong influence of background climate conditions. With projected shifting precipitation patterns and more frequent droughts and heatwaves in the future (Huang et al, ; Wuebbles et al, ), a large expansion of irrigation would be required to sustain current maize yield trends in the United States (DeLucia et al, ; McDonald & Girvetz, ). Within this context, irrigation effects are expected to be intensified, leading to a greater synergistic effect of crop yield increase and cooling benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The spatiotemporal variations in the irrigation effect found in our results highlight the strong influence of background climate conditions. With projected shifting precipitation patterns and more frequent droughts and heatwaves in the future (Huang et al, ; Wuebbles et al, ), a large expansion of irrigation would be required to sustain current maize yield trends in the United States (DeLucia et al, ; McDonald & Girvetz, ). Within this context, irrigation effects are expected to be intensified, leading to a greater synergistic effect of crop yield increase and cooling benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of the relationships between (i) the Köppen-Geiger climate type classification (Kottek et al, 2006) shown in Fig. 1 and (ii) certain model characteristics on SPI-n were quantified using a variety of tests.…”
Section: Timescales Of Drought Propagationmentioning
confidence: 99%
“…The United States is one of the most affected countries by weather hazards, and has experienced an increase in economic losses and human casualties in recent decades (Kunkel et al 1999b, Gall et al 2011Wobus et al 2014). This has motivated a number of studies examining the changes, impacts and the underlying mechanisms of extreme weather hazards (Pielke and Downton 2000;Jonkman 2005;Ashley and Ashley 2008;Changnon 2008Wobus et al 2014Leng et al 2016;Huang et al 2017;Zhou et al 2017). However, most of previous studies were hazard specific, based on a single type of indicator (e.g.…”
Section: Introductionmentioning
confidence: 99%